Study of heat transfer characteristics of SIO2 nanoparticles in heat pipes - Sarimila A/P Kannakasavei (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project deal with study of heat transfer characterisrics of silicon oxde, Sio2 in heat pipe. To achieve better performance of heat pipe, increasing its efficiency is achallenge nowadays. Effects of implemantation of nanoparticles on efficiency of heat pipe have been studied in this priject. Concept of heat tranfer applied in oder to analyse characteristic of nanofluid.